Determining Optimal Fluorescent Agent Concentrations in Dental Adhesive Resins for Imaging the Tooth/Restoration Interface - Bim Junior, Odair; Cebim, Marco A. [UNESP]; Atta, Maria T.; Machado, Camila M.; Francisconi-dos-Rios, Luciana F.; Wang, Linda (Cambridge Univ Press, 2017)
Fluorescent dyes like Rhodamine B (RB) have been used to identify the spatial distribution of adhesive restorative materials in the tooth/restoration interface. Potential effects of the addition of RB to dental adhesives were addressed in the past, but no further information is available on how to determine suitable concentrations of RB in these bonding agents for imaging in the confocal laser scanning microscope. This study provides systematical strategies for adding RB to viscous dental adhesive resins, focusing on the determination of the lowest range of dye concentrations necessary to achieve an acceptable image of the dentin/adhesive interface. It was demonstrated that optimized images of the resin distribution in dentin can be produced with 0.1-0.02 mg/mL of RB in the (tested) adhesives. Our approaches took into account aspects related to the dye concentration, photophysical parameters in different host media, specimen composition and morphology to develop a rational use of the fluorescent agent with the resin-based materials. Information gained from this work can help optimize labeling methods using dispersions of low-molecular-weight dyes in different monomer blend systems.
Keywords: confocal laser microscopy; dental adhesives; dentin bonding; fluorescent dyes; photoluminescence spectroscopy; interfacial morphology